Identification of Single Nucleotide Polymorphism on Bone Morphogenetic Protein 2 Gene in Non-Syndromic Cleft Lip/ Palate Patient - Mala Kurniati; RM Coen Pramono D; Agung Sosiawan; David Sontani Perdanakusuma; Hari Basuki Notobroto; Andra Rizqiawan (Institute of Medico-legal Publications Pvt Ltd, 2021)
Cleft lip/palate (CL/P) is one of the most common birth defects in humans. Haploinsufficiency in genesBone Morphogenetic Protein (BMP) 2 is thought to play an important role in the incidence of CL/P. Thisstudy aimed to identify changes in the nucleotide (Single Nucleotide Polymorphism/SNP) BMP 2 rs235768A>T gene in CL/P patient in Indonesia. Seventy samples of DNA that were successfully amplified andrestricted consisted of patient and control samples with the three of which were used for sequencing. Basedon the analysis using restriction enzymes and Finch TV and Bioedit software programs, this study identifieda change from nucleotide A to nucleotide T which is a mutation missense (Serine-Arginine/TCA-TCT).Based on the results of the Fisher’s exact test, there was difference in genotype frequency between the CL/Pgroup and the control. Meanwhile, there was no difference in allele frequencies between the two groups. Theallele frequency T has a higher value than the frequency of the allele A.